2022
DOI: 10.1111/zph.12995
|View full text |Cite
|
Sign up to set email alerts
|

Use of antibiotics in patients who were attacked by animals that can transmit rabies

Abstract: Animal bites pose a major public health problem for children and adults worldwide (World Health Organization., 2018) and constitute up to 1% of all visits to emergency departments (Jaindl et al., 2016;Morzycki et al., 2019). The vast majority of bite injuries are caused by dogs and, to a lesser extent, by cats, monkeys, snakes and humans (Medeiros & Saconato, 2001;Williams et al., 2021). It has been estimated that the risk of being bitten by a domestic animal throughout life is approximately 50%, but only bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Additionally, in this report, it was identified that patients who presented pain were also more likely to inappropriately receive antibiotics. This is in line with what was described in an investigation on the use of antibiotics in patients with animal bites, in which it was shown that those who were prescribed analgesics had a higher risk of receiving an antibiotic not recommended by the guidelines [29].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, in this report, it was identified that patients who presented pain were also more likely to inappropriately receive antibiotics. This is in line with what was described in an investigation on the use of antibiotics in patients with animal bites, in which it was shown that those who were prescribed analgesics had a higher risk of receiving an antibiotic not recommended by the guidelines [29].…”
Section: Discussionsupporting
confidence: 90%
“…However, it is common in the literature to find resistance to first-and second-generation cephalosporins, aminopenicillins with beta-lactamase inhibitors, and oxacillin, among others. [14][15][16] In Colombia, the use of antibiotics for unapproved indications is common, [29][30][31] a condition that leads to adverse clinical (increased length of hospital stay, morbidity, mortality, and antimicrobial resistance) and economic (increased costs of care) effects. 32 Thus, it is important to highlight that, in this study, the inappropriate use of antibiotics prevailed in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Colombia, the use of antibiotics for unapproved indications is common, 2931 a condition that leads to adverse clinical (increased length of hospital stay, morbidity, mortality, and antimicrobial resistance) and economic (increased costs of care) effects. 32 Thus, it is important to highlight that, in this study, the inappropriate use of antibiotics prevailed in most patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected patients underwent a manual review of their medical records to identify sociodemographic, clinical and pharmacological variables of interest (Valladales-Restrepo et al, 2022).…”
Section: Response To the Letter To Editor: Systemic Corticosteroid Us...mentioning
confidence: 99%